Ceiling culture of human mature white adipocytes with a browning agent: A novel approach to induce transdifferentiation into beige adipocytes - He, Yufei; Liang, Zhuokai; Wang, Jing; Tang, Haojing; Li, Jian; Cai, Junrong; Liao, Yunjun (Frontiers in Bioengineering and Biotechnology, 2022)
Excess and dysfunctional adipose tissue plays an important role in metabolic diseases, including obesity, atherosclerosis and type 2 diabetes mellitus. In mammals, adipose tissue is categorized into two types: white and brown. Adult brown tissue is mainly composed of beige adipocytes, which dispose of stored energy as heat and have become increasingly popular as a therapeutic target for obesity. However, there is still a paucity of cell models that allow transdifferentiation of mature white adipocytes into beige adipocytes, as seen in vivo. Here, we describe a novel, ceiling culture-based model of human mature white adipocytes, which transdifferentiate into beige adipocytes under the mechanical force and hypoxia of ceiling culture. We also show that the use of rosiglitazone and rapamycin can modulate transdifferentiation, up and down regulating expression of beige adipocyte-specific genes, respectively. Rosiglitazone additionally facilitated the upregulation of fatty acid lipolysis and oxidation genes. Finally, these beige adipocytes derived from dedifferentiated adipocytes exhibited a progenitor-specific phenotype, with higher expression of mature adipocyte-specific genes than adipocyte-derived stem cells. Overall, we report a novel approach to conveniently cultivate beige adipocytes from white adipocytes in vitro, suitable for mechanistic studies of adipose biology and development of cell and drug therapies in the future.